Innovation in maintenance contracts: structuring opex-based models for profitability and sustainability via led lighting projects - Machado, Leandro Mendes (Revista Sistemática, 2024)
Contracts that shift costs from capital expenditure (CAPEX) to operational expenditure (OPEX) are increasingly utilized in LED lighting projects to align provider-client incentives, spread risk, and promote both environmental sustainability and financial return. Based on empirical studies of energy performance contracting (EPC) and contract design in large energy infrastructure, this article examines how to structure OPEX-oriented maintenance contracts, particularly for LED lighting, to generate profit and sustainable outcomes. It discusses performance risk quantification, contract clause design, lifecycle cost management, and the interplay between owner and contractor preferences. Findings from literature suggest that properly balanced contracts, with clear measurement and verification, risk sharing, and inclusion of operability and maintainability criteria, can reduce total operational costs and improve contract profitability.